Yield maximization of maize through nutrient management - Mahamood, NU; Ferdous, Z; Anwar, M; Ali, R; Sultana, M (Progressive Agriculture, 2017)
Unbalanced use of chemical fertilizer is a problem in the intensive cropping systems on the Northern part of Bangladesh. Proper nutrient management is essential to maximize maize production and sustain agricultural production while minimizing negative impacts on the soil fertility. The aim of the present study was to investigate nutrient dynamics, maize yields and soil fertility in response to balanced fertilization. A field experiment (20092010) was conducted at FSRD site Lahirirhat, OFRD, Rangpur during rabi season 2009-2010 to evaluate Maximizing maize production through nutrient management. Five treatments viz.T1= N300P50K150S30, T2=P50K150S30, T3= N300K150S30, T4= N300P50S30 and T5= N300P50K150were evaluated for this purpose. The result indicated that the highest grain yield (8.37 t/ha) was found from T1= N300P50K150S30 treatment. The lowest grain yield (7.33 t/ha) was obtained from T2=P50K150S30 treatment. The gross return (Tk.100107/ha) and gross margin (Tk.44951/ha) was higher with T1 and T3 treated plot. It may be concluded that proper nutrient management may be the good alternatives for maximizing maize yield and management of soil health at Rangpur region in Bangladesh. Progressive Agriculture 27 (4): 428-434, 2016